The Relationship Between Modern Technology And Social Morality: An Analysis Of Islamic Religious Education And Digital Literacy In the Kuntu Darussalam Community - Nurul Habibah Arfizeah; Z. Zarkasih; Rian Vebrianto (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The phenomenon of modern technological development in society shows significant changes in patterns of communication, social interaction, and access to information. Rapid technological advancement should not be separated from social morality grounded in Islamic Religious Education (PAI). The integration of PAI and digital literacy is expected to guide society in using technology positively, strengthening social ethics, and preventing negative impacts such as the misuse of social media, the spread of invalid information, and the weakening of ethical control in digital interactions. This study aims to analyze the relationship between modern technology and social morality through the integration of PAI and digital literacy using a mixed-method approach with a case study design. The subjects included 30 respondents and two key informants from diverse backgrounds. Data were collected through questionnaires and dyadic in-depth interviews and analyzed both quantitatively and qualitatively. The results indicate that the level of public understanding is very high, with an average score of 4.63, demonstrating the community’s ability to integrate PAI values into ethical and responsible technology use. However, challenges remain, including reduced in-person social interaction and limited digital literacy among some members. Overall, this integration requires continuous educational support.